Robot-assisted resection for cancer in the remnant stomach: a report of 11 cases - Feng Qian (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: The aim of this study was to investigate the technical feasibility and clinical therapeutic effects of robotassisted resection for cancer in the remnant stomach (CRS). Methods: Robot-assisted resection was performed on 11 patients with CRS. Patient demographics, operative data and short-term effect were examined and a short-term follow up was also performed. Results: All operations were performed by an experienced surgeon successfully without intraoperative mortality. D2 radical resection of remnant stomach was performed on 9 patients, and palliative resection was performed on 2 patients. There were 2 cases of conversion from robotic surgery to open surgery. Rouxen- Y esophagojejunostomy was performed in all cases for digestive tract reconstruction. Conclusion: Robot-assisted resection of GSC is technically feasible and has good shortterm outcomes. The results of long-term follow-up are needed to confirm the feasibility of robotic remnant gastrectomy.